2020
DOI: 10.1038/s41467-020-16799-0
|View full text |Cite
|
Sign up to set email alerts
|

ADNP promotes neural differentiation by modulating Wnt/β-catenin signaling

Abstract: ADNP (Activity Dependent Neuroprotective Protein) is a neuroprotective protein whose aberrant expression has been frequently linked to neural developmental disorders, including the Helsmoortel-Van der Aa syndrome (also called the ADNP syndrome). However, its role in neural development and pathology remains unclear. Here, we show that ADNP is required for neural induction and differentiation by enhancing Wnt signaling. Mechanistically, ADNP functions to stabilize β-Catenin through binding to its armadillo domai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 38 publications
6
61
1
Order By: Relevance
“…It appeared that alteration of chromatin accessibility of POGZ-bound genes did not always lead to gene expression change. This was also observed in OCT4- and ADNP-depleted ESCs where much more dramatic change in chromatin accessibility occurred (King and Klose, 2017; Ostapcuk et al, 2018; Sun et al, 2020).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…It appeared that alteration of chromatin accessibility of POGZ-bound genes did not always lead to gene expression change. This was also observed in OCT4- and ADNP-depleted ESCs where much more dramatic change in chromatin accessibility occurred (King and Klose, 2017; Ostapcuk et al, 2018; Sun et al, 2020).…”
Section: Resultsmentioning
confidence: 66%
“…The down-regulation of neuroectodermal lineage genes during ESC EB formation was of great interest to us, considering that mutations of POGZ are frequently linked with neurodevelopmental disorders such as autism syndrome disorders (ASD) (Matrumura et al, 2020; Nozawa et al, 2018), which strongly suggested that POGZ is required for early neural induction by promoting neural progenitor genes (NPGs). To investigate this, we directly differentiated control and Pogz-/- ESCs into neural spheres for a time course of 7 days, using our previously published method (Sun et al, 2020). As shown in Figure 2G, the expression levels of NPGs were markedly decreased in Pogz-/- ESC derived neural progenitors compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…The Wnt/β-catenin pathway is evolutionarily well-conserved, and aberrant activation of this pathway can cause abnormal cell growth and malignant transformation (Clevers and Nusse, 2012;Sun et al, 2020). Wang et al (2019) revealed that the novel lncRNA OTUD6B-AS1 decreased the activity of the Wnt/β-catenin pathway and suppressed the expression of EMT-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…HPSCs were initially treated with BMP4 and WNT agonists (WNT3a or the small molecule CHIR99021) for 3 days, and the expression of T, a primitive streak and early mesodermal marker, was monitored daily (Figure 1a; Supplementary Figure 1a-b). CHIR99021 is a highly specific glycogen synthase kinase-3 (GSK3) inhibitor that can activate canonical Wnt signaling (Sun et al, 2020). Compared to the treatment with BMP4 or WNT3a only, combined treatment with BMP4 and WNT3a resulted in a quick induction of T, reaching its maximum expression levels at day 1 ( Supplementary Figure 1a).…”
Section: Efficient Generation Of Isl1 + Cardiac Progenitor Cells Frommentioning
confidence: 99%
“…ChIP experiments were performed according to the Agilent Mammalian ChIP-on-chip manual as described (Sun et al, 2020). Briefly, 1x10 8 cells were fixed with 1% formaldehyde for 10 min at room temperature.…”
Section: Chromatin Immunoprecipitation (Chip)mentioning
confidence: 99%